Pengaruh NPF, ROA dan CAR Terhadap Financial Distress Dengan GCG Sebagai Pemoderasi - Riska Aulia; Abdullah, Muh. Wahyuddin; Fajrin, Farid (Journal of Accounting, Economics, and Business Education, 2024)
The aim of this research is to determine the influence of NPF, ROA and financial distress which is moderated by good corporate governance. Financial distress is a decline in the financial condition of a bank which will ultimately result in bankruptcy. Financial distress conditions were analyzed using the Altman z-score method based on the financial reports of Islamic commercial banks in Indonesia, Malaysia and Brunei Darussalam. The sample in this study was 40 Islamic commercial banks. The type of research used is quantitative research with a causality approach. The sampling technique is purposive sampling. The data analyzed is in the form of sharia commercial bank financial reports for the 2018-2022 period. The results of this study show that non-performing financing and capital adequacy ratio have no effect on financial distress, while Return on Assets have a negative effect on financial distress. Then good corporate governance cannot moderate the influence of non-performing financing and Return on Assets on financial distress. Meanwhile, the influence of the capital adequacy ratio on financial distress can be moderated by good corporate governance.